The Relationship between Sleep Quality and Emotional Intelligence among Nurses in Denpasar - Kanifah, Laleatul; Hartika, Listiyani Dewi; Wiriana (LPPM Universitas Dhyana Pura, 2025)
This study explores the relationship between sleep quality and emotional intelligence among nurses in Denpasar. Sleep quality encompasses duration, depth, and efficiency, while emotional intelligence includes self-awareness, self-regulation, motivation, empathy, and social skills. Using a quantitative correlational design, the study involved 73 nurses selected through simple random sampling. Instruments used were the Pittsburgh Sleep Quality Index (PSQI) and an emotional intelligence scale based on Goleman's model. Data were analyzed using Pearson's correlation test, revealing a positive and significant relationship between sleep quality and emotional intelligence. Interestingly, even with reduced sleep quality, nurses demonstrated improved emotional intelligence, suggesting a potential adaptive response that may positively influence healthcare service quality.